CO2 highways for Europe modeling a carbon capture, transport and storage infrastructure for Europe - Roman Mendelevitch; Johannes Herold; Pao-Yu Oei; Andreas Tissen (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We present a mixed integer, multi-period, cost-minimizing carbon capture, transport and storage (CCTS) network model for Europe. The model incorporates endogenous decisions about carbon capture, pipeline and storage investments; capture, flow and injection quantities based on given costs, certificate prices, storage capacities and point source emissions. The results indicate that CCTS can theoretically contribute to the decarbonization of Europe's energy and industry sectors. This requires a CO2 certificate price rising to 55 in 2050, and sufficient CO2 storage capacity available for both on and offshore sites. However, CCTS deployment is highest in CO2-intensive industries where emissions cannot be avoided by fuel switching or alternative production processes. In all scenarios, the importance of the industrial sector as a first mover to induce the deployment of CCTS is highlighted. By contrast, a decrease of available storage capacity or a more moderate increase in CO2 prices will significantly reduce the role of CCTS as a CO2 mitigation technology, especially in the energy sector. Continued public resistance to onshore CO2 storage can only be overcome by constructing expensive offshore storage. Under this restriction, to reach the same levels of CCTS penetration will require doubling of CO2 certificate prices.
Keywords: C61; H54; O33; 330; Carbon capture and storage; pipeline; infrastructure; optimization; Kohlenstoffsenke; Leitungstransport; Netzwerk; Ganzzahlige Optimierung; Emissionshandel; EU-Staaten